ANALISIS PENILAIAN TRIAGE DAN REVISED TRAUMA SCORE DALAM MEMPREDIKSI MORTALITAS PADA PASIEN TRAUMA KEPALA - Maulida, Aima Nur; Khotimah, Khotimah (Jurnal EDUNursing, 2019)
ABSTRACTImproper handling of management systems and quickly increase mortality in head injuries. Triage assessment can reduce the risk of death. However, triage is at risk of undertriage which can increase mortality. A more detailed assessment system is needed, so Revised trauma score (RTS) can be used to minimize undertriage. The purpose of this study is to analyze the triage assessment and RTS assessment in predicting mortality in cases of head trauma. The study design was observational analytic with cross sectional approach. The population was all head trauma patients in the emergency room at Jombang Regional Hospital with 121 patients. The sample consisted of 89 respondents taken using Simple Random Sampling. The research instrument used observation sheets. Data were analyzed using Chi-square test with a significance level of p <? (? = 0.05). The results of the triage and mortality assessment show a significance value of p = 0.00 (p <?), meaning that there is a relationship between the triage assessment and mortality. While the RTS assessment shows a significance value of p = 0.00 (p <?) so that, it means that there is a relationship between RTS assessment and mortality. Triage assessment can speed up the handling of head trauma and RTS can know the physiological status so as to determine an accurate action. Both triage assessment and RTS can predict mortality risk in head injuries.Keywords: Head trauma, triage, Revised Trauma Score (RTS), mortalitas.